PRODUCTION AND PURIFICATION OF A THERMOSTABLE LIPASE FROM A HYPERACTIVE BACTERIAL ISOLATE BREVIBACILLUS SP. FROM TAPTAPANI HOT SPRING, ODISHA - ASHOK KUMAR PANIGRAHI,; AMRITA KUMARI PANDA,; S.P.S. BISHT, (International Journal of Pharma and Bio Sciences, 2014)
Thermostable lipase producing Brevibacillus sp. was isolated from Taptapani hot water spring of Ganjam, Odisha, India. Maximum lipase production by Brevibacillus sp. was obtained at pH 10 when grown under shaking condition at 60 °C for 30 hrs. To enhance the production of lipase, nutritional factors were optimized and it was observed that maximum lipase production was obtained in the presence of ammonium ferric sulfate as the best inorganic nitrogen source. Out of various natural and synthetic triglycerides used, olive oil was found as the most suited substrate for the production of extracellular lipase. In addition to this the carbon source maltose added in this study significantly increases the lipase production. The 2.83 fold purification of the lipase enzyme from this strain with 70% recovery achieved by ammonium sulphate saturation and Phenyl Sepharose column chromatography (specific activity; 2.1U/mg of protein with a molecular weight of 70 kDa) as a single step purification process. It is the first report that a genus Brevibacillus produces large lipase with a size of approximately 70 kDa.